THE INFLUENCE OF WAGES AND OVERTIME INCENTIVES ON CV WORKER JOB SATISFACTION. SWL PAGAR MERBAU DELI SERDANG - Suryani Rambe; Hablil Ikhwana; Zulaili (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine whether the amount of wages and overtime incentives, both partially and simultaneously, have a significant effect on job satisfaction of CV. SWL Pagar Merbau Deli Serdang workers and how big the effect is. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the results of primary data regression processed using SPSS 25, the following multiple linear regression equation is obtained: Y =5,425+ 0.181X1 + 0.689X2 + e. Partially, the wage amount variable (X1) has a significant influence on the job satisfaction of CV. SWL Pagar Merbau Deli Serdang workers, as evidenced by the calculated t value > t table (2,530> 2.018). The overtime incentive variable (X2) has a significant influence on the job satisfaction of CV. SWL Pagar Merbau Deli Serdang workers, as evidenced by the calculated t value > t table (8,832> 2.018). Simultaneously, the variables of wage amount (X1) and overtime incentive (X2) have a significant influence on the job satisfaction of CV. SWL Pagar Merbau Deli Serdang workers. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (56.946 > 3.22). The variables of wage amount (X1) and overtime incentive (X2) are able to contribute to the influence of the variable of job satisfaction of CV. SWL Pagar Merbau Deli Serdang workers by 73.1% while the remaining 26.9% is influenced by other variables not examined in this study. From the conclusion above, the author suggests that the wages received by workers greatly influence job satisfaction, the amount of wages can be increased and maintained in the form of improving the quality of work by achieving targets set by the company. The level of overtime incentive provision is based on the length of employee work and work targets, therefore, it needs to be increased and improved according to the workload given to employees. Company leaders greatly influence worker job satisfaction by providing additional wages to workers to improve worker job satisfaction so that the quality of worker work is better.